Micropropagation Live Pharmacy for Chronic Non-Communicable Diseases Program: The Construction of a New Model Organic Food Production and Medical Plants in Urban Farms - Neves C; Penna TCV (Public Health, 2025)
The Micropropagation live Pharmacy for Chronic Non-communicable Diseases (CND) Program (PFVMDCNT) arises as a new strategy to promote CNDs treatment by buil-ding green and healthy environments in order to improve public health through prevention by healthy diet and rational use of medicinal plants. Based on these assumptions, this article aims to reflect on the PFVMDCNT potential and contradictions in the changing process of the cur-rent agricultural production model of conventional living pharmacies for the micropropagation model here proposed. This study involves a descriptive-reflexive methodology, presenting two literature based themes: the origins of Brazil’s living pharmacy programs historical review and new trends such as urban farms and vertical gardens, with special attention to the PFVMDCNT.